Infectious diseases surveillance in Pakistan: Challenges, efforts, and recommendations. (June 2022) - Bilal, Wajeeha; Qamar, Khulud; Abbas, Samina; Siddiqui, Amna; Essar, Mohammad Yasir
Abstract: Public health remains a major concern in Pakistan, with communicable diseases including HIV/AIDS, hepatitis B, and C, and tuberculosis the leading cause of morbidity and mortality. Several factors contribute to the country's high risk of infectious disease epidemics, including overcrowded cities, unclean drinking water, inadequate sanitation, poor socioeconomic conditions, and low vaccination coverage. Due to the absence of a comprehensive surveillance strategy and mechanism, it has been difficult to manage infectious disease outbreaks effectively. The article offers insights into the various challenges faced by public and private healthcare sectors to control the spread of communicable diseases and proposes solutions to prevent crippling of the overburdened healthcare system on a national scale.